(3GdefUhQi aj GdWHs - (3eMeO Hf RcQjG GdnqQGRj, CHh HcQ,J (B311 (3g` s
(3ChdgG (B:s
(3ai Mei GdOb , ai Mei GdZH , ai Mei GdeMQbI , ai Mei GdeWHbI ai Mei GdHdZejI , ai Mei GdQHY ai GdMejGJ GdJi NeSkG hSOSkG aUGYOG, hgj GdeNJdWI ai GdMejGJ GdOGFeI s
(3BNQgG (B:s
(3JUjQ gPg GdCOhjI hJdbi ajg YfO GdWM Ef TGA Gddg JYGdi JeJ GdebGdI GdYGTQI ef cJGH GdefUhQi HJeGe LejY GdOjhGf hGdMeO ddg cKjQkG s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3GdJhKjbGJ GdeQLYjI (B:s
GAL - (3GdLRA (B1 - (3U (B234 ; GAL - (3GdLRA (B1 - (3U (B419 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B256 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdWHs